(untitled) (Journal of Environmental Science and Natural Resources, 2015)
A study was carried out with 25 pond water samples of Bhola Sadar Upazila to assess the quality of surface water for irrigation, aquaculture, drinking and livestock consumption. Chemical analyses of different parameters were done to assess the quality of water. All of the water samples showed slightly acidic in nature. Sixteen surface water samples were not suitable for drinking and aquaculture in respect of pH (pH <6.5). Electrical conductivity (EC) categorized the waters as low salinity (C1) to medium salinity (C2) class for irrigation. With respect to total dissolved solids surface waters were within highest desirable limit for drinking and irrigation and suitable for livestock consumption and aquaculture. Calcium and Magnesium content rated the samples as maximum permissible and highest desirable limit for drinking. All the samples were suitable for drinking in case of Na and K, 21 samples were not suitable for aquaculture due to higher (>5.0 mg L-1) K content. Six samples were unsuitable for livestock due to higher (Cl >30mgL- 1) Cl values. SSP rated 9 samples as good, 1 as excellent, 6 as doubtful and 9 as permissible for irrigation. With respect to RSC 21 samples were suitable, 3 were marginal and 1 was unsuitable for irrigation. Hardness classified 14 samples within moderately hard, 10 within soft and only one as hard limit for irrigation and 1 sample (No. 16) was unsuitable for livestock consumption. P, B, Cu and As concentration categorized all the samples suitable for irrigation, aquaculture, drinking and livestock consumption. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22053 J. Environ. Sci. & Natural Resources, 6(1): 131-140 2013